Analisis Ketahanan Material Epoxy Powder EF150AB pada Uji Thermal Shock untuk Komponen Charger Mobil Listrik - Apang Djafar Shieddique; Amri Abdulah; Choerul Anwar; Yoon Jung Rag; Sohn Chang Kil; Dodi Muhammad (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa & Inovasi, 2021)
Inside the electric car charger there is a controller where one of the components is the Disc Ceramic Capacitor (DCC) type SCF2E472M10 coated with epoxy powder EF150AB. The faster the charging, the higher the temperature, for that we need good performance on the capacitor layer. The method used in this study is to test the Pressure Cycle Temperature (PCT) with a temperature of 121 ° C, a pressure of 2 bar and a holding time of 48 hours and a Thermal Shock Test with a temperature parameter of -40 ° C to 125 ° C for each temperature change. 30 minutes for 100 hours, the number of test samples for each test is 20. From the test results, it was found that the average capacitance value on the PCT test was 4439.9 pF with a standard limit value of 3760 to 5640 pF, then the average value of Insulation resistance (IR) after the PCT test was 14183 Ω with the standard limit of the IR value of 10000 Ω. From these results it can be concluded that epoxy powder EF150AB is good for DCC coatings because the coating is resistant to low and high temperatures, which ranges from -40 ° C to 125 ° C.